Just Energy Transition dalam Hubungan Internasional Kontemporer: Debat, Kontestasi, dan Politik Keadilan Global - Asep Agil Supriatna; Wildan Ilmanuarif Shafar (Yayasan Lentera Avanya Nagari, 2026)
This article maps the Just Energy Transition (JET) debate in contemporary International Relations (IR) literature and identifies its fundamental conceptual contestations. Using qualitative document analysis combined with reflexive thematic analysis of peer-reviewed publications from 1995 to 2025, this study purposively selected literature representing diverse IR theoretical approaches and Global North-South perspectives. The analysis identifies four main themes: International Political Economy and Global Governance, Political Ecology and Energy Justice, Energy Democracy and Socio-Technical Transitions, and Public Policy and Development Studies. Their interaction produces four conceptual contestations: reform versus structural transformation, universalism versus normative particularism, speed versus inclusivity, and epistemic asymmetry between the Global North and Global South. The findings demonstrate that JET is not merely a technical policy matter but a field of global political contestation reflecting deep ontological and epistemological differences about justice, power, and world order transformation. This study contributes the first systematic conceptual mapping of JET debates from an IR lens. Artikel ini memetakan perdebatan Just Energy Transition (JET) dalam literatur Hubungan Internasional (HI) kontemporer dan mengidentifikasi kontestasi konseptual fundamentalnya. Menggunakan analisis dokumen kualitatif dengan reflexive thematic analysis terhadap publikasi peer-reviewed periode 1995-2025, penelitian ini memilih literatur secara purposif yang merepresentasikan beragam pendekatan teoretis HI serta perspektif Global North dan Global South. Analisis mengidentifikasi empat tema utama: Ekonomi Politik Internasional dan Tata Kelola Global, Ekologi Politik dan Keadilan Energi, Demokrasi Energi dan Transisi Sosio-Teknis, serta Kebijakan Publik dan Studi Pembangunan. Interaksi antarkeempat tema menghasilkan empat kontestasi fundamental: reformasi versus transformasi struktural, universalisme versus partikularisme normatif, kecepatan versus inklusivitas, serta asimetri epistemik Global North-South. Temuan menunjukkan bahwa JET dalam perspektif HI bukan sekadar persoalan teknis-kebijakan, melainkan arena kontestasi politik global yang mencerminkan perbedaan ontologis dan epistemologis mengenai keadilan, kekuasaan, dan transformasi tatanan dunia.